Emotional validation and affective bonding in early childhood education: design and pilot of a training program in Spain and Costa Rica - Vargas Pana, Carolina; Gijón Puerta, José; Lizarte Simón, Emilio Jesús (Frontiers in Education, 2025)
Emotional development in childhood is an aspect of undeniable importance, considering that this is a key stage for the acquisition of the emotional and social skills required for life in society. This study analyzes the effects of implementing a teacher training program for children's emotional development based on the establishment of emotional bonds and the validation of emotions in early childhood education. The strengthening of children's emotional development—focused on the establishment of emotional bonds and the validation of emotions—increases the number of interactions linked to these processes, especially those of emotional validation. The objective of this research was to analyze the effectiveness of a program developed to strengthen children's emotional development—focused on the establishment of emotional bonds and the validation of emotions. A quasi-experimental pretest-posttest design was used, focusing on comparing pre- and post-intervention results between an experimental and a control group in two international contexts (Spain and Costa Rica). The evaluation of the training program’s effect, carried out in both groups, included a pretest and posttest of the abbreviated and translated into Spanish scale of the Student-Teacher Relationship Scale (STRS), as well as a record of the frequency of emotional validation actions during three days of classroom work. The data were analyzed with descriptive statistical tests and various types of analysis to analyze the intervention effects using Mixed Effects Models. The pretest and posttest analyses showed a significant improvement in some of the aspects of affective bonding measured with the Student-Teacher Relationship Scale (STRS) and an increase in emotional validation actions present in teacher-child interactions. These findings suggest that a teacher training program focused on emotional validation and strengthening affective bonds can lead to greater closeness between teachers and children, as well as a reduction in classroom conflicts.